Methods of Modeling Syntactic Relations (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article explores the classification and modeling of syntactic relations within sentence structures using junctional models. Drawing on theoretical frameworks from linguists like A.M. Mukhin, the paper categorizes syntactic relationships into seven types: nuclear predicative, subordinative, coordinative, non-nuclear predicative, appositive, zero-predicative, and introductive. Each type is defined, illustrated with examples, and represented visually via diagrammatic models that reflect syntactic dependencies. The paper also links these relationships to the broader concept of syntactic valency, emphasizing how sentence components interact both structurally and functionally. The analysis is presented from both componential and syntaxeme-level perspectives.